Current concepts in robotic total hip arthroplasty - Kouyoumdjian, Pascal (SICOT J, 2020)
Introduction: Total hip replacement provides mostly fair functional and clinical results. Many factors play an essential role in hip stability and long-term outcomes. Surgical positioning remains fundamental for obtaining accurate implant fit and prevent hip dislocation or impingement. Different categories of robotic assistance have been established throughout the previous years and all of the technologies target accuracy and reliability to reduce complications, and enhance clinical outcomes. Materials and methods: An overview is proposed over the principles of robotic assistance in hip arthroplasty surgery. Accuracy, reliability, management of the bone stock, clinical outcomes, constraints and limits of this technology are reported, based on recent literature. Results: Potential advantages regarding pre-operative planning accuracy, cup positioning, maintenance of the center of rotation, preservation of an adequate bone stock nay clinical short- and mid-term outcomes are balanced with some reported disadvantages and limits like hip anatomical specificity, cost-effectiveness, engineering dependence. Discussion: The use of robotic-assisted THA presents clear and evident benefits related to accurate implant positioning and maintenance of a minimal bone while allowing. For some authors, an early improvement in functional results and patient’s recovery. This technology demonstrated a shorter surgical time and a short learning curve required to optimize its use and this technology presents promising outcomes and results and potential use in routine clinical application but its limitation of use is still present especially the cost of the robot, the need for the presence of an engineer during the surgery, its availability of use in all hospitals as well as the difficulty presented in dysplastic or dysmorphic hip joints.